Crystalquasichemical Description the Formation of Defects in nanodispersed Yttrium-Iron Garnet - V. D. Fedoriv; N. V. Stashko; I. P. Yaremiy; L. V. Turovska (Фізика і хімія твердого тіла, 2017)
By the sol-gel method of autocombustionan initial oxide system was synthesized for a receipt a nanodispersed Yttrium Iron Garnet. It was set that forming of the monophase system Y3Fe5O12begins at temperatures above 973 К in static air atmosphere. The crystalquasichemical formulas for Y3Fe5O12 are offered. Dependence of concentration of defects from a degree non-stoichiometry of oxygen is calculated. It was set that the formation of garnet structure needed oxygen atmosphere annealing. Partial pressure of oxygen determines the resulting structure defects. Keywords: yttrium iron garnet, sol-gel-autocombustion method, isothermal annealing, atmosphere, crystalquasichemical formulas, defects.